PENGARUH PROGRAM KAMPANYE âSAY NO TO PLASTIC BAGâ OLEH THE BODY SHOP TERHADAP PARTISIPASI MASYARAKAT - Anggani, Calisca Hardiana (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2014)
background this study is that the PR from The Body Shop Indonesia working together with IDdkp ( IndonesiaDiet Plastic Bags ) finalize program aims to foster community participation in efforts to maintain environment byreducing and wiser in the use of plastic bags .In addition , with this campaign of The Body Shop as well as introducing to the people that they truly are a cosmeticsmanufacturer that care about the environment and the products and their packaging is also environmentallyfriendly and do not use plastic as raw material. The purpose of this study was to determine the magnitude influencePR campaign created by The Body Shop is against participation community and know how effective the programis in foster public participation in the reduction of the use of plastic bags with bring your own shopping bag orreplace it with a more pocket a green .As a cornerstone of this study , used campaign then got the effect that the communicant can do things likethat desirable communicator . Then I also use participation Theory This study uses a quantitative methodologyexplanative survey as a means of taking the sample . This research was conducted in the media social twitterfollowers with the subject is the twitter account of The Body Shop Indonesia. Sampling technique takingsimple random sampling , with reference using Taro Yamane formula . For data collection techniques throughquestionnaire ( questionnaire ) and literature . For data analysis , the authors using SPSS ( Statistical Packagefor Social Science ) .